The effects of library education on information seeking behaviour of first-year students at the University of Ibadan, Nigeria (2016)
This study was carried out to investigate barriers encountered by fresh students in seeking information and the extent to which library user education can help in improving their information seeking behaviour at the University of Ibadan. The actual utilization of resources in the library remains inconsistent, low and unsatisfactory. Considering that low utilization of library resources undermines the huge investment on library resources and personnel retention, this study has examined the barriers encounter by students in information seeking and the extent to which library orientation can help in improving information seeking behaviour of first year undergraduate students at the University of Ibadan. Survey research design was adopted for the study. Using a systematic sampling technique, a total of 230 first year students drawn from six faculties participated in the study. Results show that majority of first year students participated in use education in KDL but encounter information seeking challenges in the library. Because of poor perception of the library which makes them doubt the ability of the library to meet their information needs. The study suggests that effective utilization of academic library resources is dependent on perceived availability of relevant information materials, proper understanding of the products and services offered by the library and user’s ability to utilize information retrieval tools and systems. The study therefore recommends a holistic approach to library orientation in colleges and universities in order to promote student’s library utilization and build up their information seeking capacity.